Differentials in Contraceptive Use Among Selected Minority Ethnic Groups in Nigeria - Ayinmoro, Aboluwaji Daniel; Fayehun, Olufunke A. (Frontiers in Global Women's Health, 2022)
Ethnicity is one of the critical factors that shape contraceptive use in Nigeria. While there are growing disparities in contraceptive uptake among women of reproductive age in the three major ethnic groups (Hausa, Igbo and Yoruba), not much is known about differentials in contraceptive use among the minority ethnic groups. This study examined differentials in contraceptive use among a sample of 1,072 respondents comprising the Ebira (352), Igala (358) and Okun (361) ethnic groups in Nigeria. Questionnaire was administered to respondents proportionately in the selected minority ethnic groups with six key informant interviews and 12 focus group discussions to generate quantitative and qualitative data among ever-married women. Quantitative data were analyzed at bivariable and multivariable levels. The qualitative data were content-analyzed. Differentials in contraception are shaped by ethnic affiliations and socio-demographic characteristics of couples. The use of modern contraceptives was low among the Ebira (25.7%) and Igala (24.1%) ethnic groups, but high among Okun (67%) women of reproductive age. The odd of using a modern contraceptive is significantly higher among the Okun women (UOR = 5.618, 95% CI 4.068–7.759) than the Ebira and Igala. There is no significant difference between the Ebira and Igala minority ethnic groups on modern contraceptive use. Ethnicity as a factor is not a stand-alone predictor of the use of modern contraception among the study groups, other socio-economic variables such as residence, religion, income and marital status were significant predictors of modern contraceptive use among minority ethnic groups. We suggest introducing reproductive health intervention programmes targeted at sensitizing the minority ethnic groups on effective modern contraceptive use while addressing their specific modern contraceptive need in Nigeria.